Improving the Discipline of Female Santri through Islamic Counseling Methods - Juwita, Salsabila (Pesantren and Community Development Studies - Islamic Institute of Syarifuddin, Indonesia., 2025)
Islamic counseling serves as a guidance service designed to assist students (santri) in understanding and appropriately responding to their personal conditions and life situations. Its practical application is prominently reflected in the cultivation of disciplinary values within pondok pesantren, where Islamic counseling methods are systematically employed to foster student compliance and behavioral order. This study aims to explore the implementation of Islamic counseling in enhancing the discipline of female students and to identify both the supporting and inhibiting factors influencing the counseling process. Utilizing a qualitative research design with a case study approach, this research presents descriptive and analytical insights derived from in-depth interviews conducted with key informants. The primary data source consists of direct narratives from participants, allowing the researcher to uncover nuanced, real-life experiences. The findings reveal that discipline and obedience are foundational in fostering respect for institutional regulations, organizational systems, and collective decision-making processes within the pesantren context. Discipline is conceptualized as a consistent commitment to adhere to established rules and codes of conduct. Moreover, the study highlights the significant role of reward and punishment mechanisms as pivotal supporting factors that strengthen student discipline through the structured application of Islamic counseling practices.